2006
DOI: 10.1007/s00586-006-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

The development of an evidence-based patient booklet for patients undergoing lumbar discectomy and un-instrumented decompression

Abstract: Post-operative management after lumbar surgery is inconsistent leading to uncertainty amongst surgeons and patients about post-operative restrictions, reactivation, and return to work. This study aimed to review the evidence on post-operative management, with a view to developing evidence-based messages for a patient booklet on post-operative management after lumbar discectomy or un-instrumented decompression. A systematic literature search produced a best-evidence synthesis of information and advice on post-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 56 publications
2
37
0
4
Order By: Relevance
“…Combined with the deconditioned state many patients present with [1,16,23,25,33,39] this may explain the low improvements in function observed. This lack of post-operative advice has now been addressed in the form of a patient education booklet [28], the value of which is currently being explored in a randomised controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the deconditioned state many patients present with [1,16,23,25,33,39] this may explain the low improvements in function observed. This lack of post-operative advice has now been addressed in the form of a patient education booklet [28], the value of which is currently being explored in a randomised controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by McGregor et al [34] conducted a systematic literature search, and reviewed the evidence on post-operative management, and found that there was a little evidence for any post-operative restrictions, and a strong case for an early active approach. This message was extracted and developed into a patient centred message in an educational booklet.…”
Section: Post-operative Care After Disc Surgerymentioning
confidence: 99%
“…The medication and conservation methods, for example complete bed rest, have generally been used for treatment after herniated nucleus pulposus (HNP) surgery, but the negative effects of these methods have often been reported 1,2) . One possible reason is that so-called deconditioning syndrome increases pain and reduces motor functions after surgery 2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason is that so-called deconditioning syndrome increases pain and reduces motor functions after surgery 2,3) . Actually, 22-70% HNP patients after surgery report sciatica and low back pain 4) which leads to restriction of movement inducing muscular atrophy, weakness, fatigue, and overload on discs of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%